Models Predicting Psychosis in Patients With High Clinical Risk: A Systematic Review - Montemagni, Cristiana; Bellino, Silvio; Bracale, Nadja; Bozzatello, Paola; Rocca, Paola (Frontiers in Psychiatry, 2020)
Objective: The present study reviews predictive models used to improve prediction of psychosis onset in individuals at clinical high risk for psychosis (CHR), using clinical, biological, neurocognitive, environmental, and combinations of predictors. Methods: A systematic literature search on Pubmed was carried out (from 1998 through 2019) to find all studies that developed or validated a model predicting the transition to psychosis in CHR subjects. Results: We found 1406 records. Thirty-eight of them met the inclusion criteria; 11 studies using clinical predictive models, 7 studies using biological models, 5 studies using neurocognitive models, 5 studies using environmental models, and 18 studies using combinations of predictive models across different domains. While the highest positive predictive value (PPV) in clinical, biological, neurocognitive, and combined predictive models were relatively high (all above 83), the highest PPV across environmental predictive models was modest (63%). Moreover, none of the combined models showed a superiority when compared with more parsimonious models (using only neurocognitive, clinical, biological or environmental factors). Conclusions: The use of predictive models may allow high prognostic accuracy for psychosis prediction in CHR individuals. However, only ten studies had performed an internal validation of their models. Among the models with the highest PPVs, only the biological and neurocognitive but not the combined models underwent validation. Further validation of predicted models is needed to ensure external validity.